Implementasi Pembelajaran Berdiferensiasi di Era Kurikulum Merdeka: Antara Harapan, Hambatan, dan Realitas di Lapangan - Nidia Winda Sari (PT PUSTAKA CENDEKIA GROUP, 2024)
This study aims to identify the implementation of differentiated instruction in the context of the Merdeka Curriculum at Indonesian high schools. Using a qualitative case study approach, observations and interviews were conducted with 10th-grade teachers who understand differentiated instruction but have not fully implemented it. The findings indicate that while teachers comprehend differentiation concepts, limited time, resources, and concerns about student gaps are significant barriers. Teachers highlighted the need for intensive training and institutional support. This study provides recommendations to enhance the Merdeka Curriculum's effectiveness by addressing students' specific needs.